Pembelajaran Toleransi: Upaya Guru Pendidikan Agama Islam dalam Menangkal Paham Radikal di Sekolah - A. Jauhar Fuad (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper intends to explain the role of PAI teachers in learning that can erode the idea of radicalism. Learning tolerance rests on constructive learning theories, with active learning, independent learning, cooperative-colaborative learning, and cognitive strategies. With the learning stage; ask, discover, community learning, modeling and true assessment. This kind of learning can encourage the open mindedness, respect differences of opinion, have a sense of understanding, and critical thinking, so that the seeds of radical understanding of students can be lost in the learning process